Scoping review of barriers and facilitators to the successful implementation of education programs that promote digital literacy among older adults in the community - Bobrowicz-Campos, E. M.; Matos, A. P. da M. (Sisyphus: Journal of Education, 2025)
This scoping review maps evidence on individual, situational, institutional and contextual factors influencing the success of digital education programs for community-dwelling older adults. Guided by the methodological recommendations of the Joanna Briggs Institute and the Population-Concept-Context framework, the review included published and unpublished studies in English, Portuguese and Spanish. From 1275 records identified, 19 met inclusion criteria. The analysis revealed a range of factors grouped as facilitators and barriers. These include learners’ disposition and capacity to engage in the learning process and their everyday circumstances (individual and situational perspectives); educator profiles, organizational and pedagogical strategies, and the availability, adaptability, and complexity of digital media and educational resources (institutional perspective); and the community’s role in encouraging the ongoing use of digital competences (contextual perspective). The findings underscore the need for a tailored and multidimensional approach, informing the development of evidence-based guidelines to support the design and implementation of education programs promoting digital literacy in advanced age.